(untitled) (Vietnam Journal of Community Medicine, 2023)
Introduction: Vietnam is on the cusp of a dramatic aging of the population. In 2015, Vietnam became an aging society. But elderly Vietnamese struggle with multiple diseases and a short healthy lifespan. Objective: This paper aimed to assess the change in the quality of life of the elderly before and after the intervention applying the "Healthy Ageing" model (period 2018-2021) in 4 communes of Chi Linh City, Hai Duong and Kim Boi district, Hoa Binh. Methods: The study used a quasi-experimental design that used data before and after an intervention to evaluate the effectiveness of the intervention. The total number of elderly participants was 1260 people with 2 data collection periods: Jan-Apr, 2018 and Jan-Apr, 2022. Findings: The results showed that quality of life scores ranged from 5.96 to 8.09, with the overall score in the intervention group (7.20) significantly higher than in the control group (6.96). Conclusions: The intervention model “Healthy ageing” showed its effectiveness in improving quality of life amongst elderly.